The situation of the Muslims of Andalusia after the fall of Granada through the efforts of Dr. Abdul Rahman Ali Al-Hajji - Hammoud Mohammed, Osama; Nuri Jawad, Raneen (Journal of College of Education, 2022)
The research dealt with the efforts of a great Iraqi historian who wrote on Islamic and Andalusian history in particular. He has several books on this and his saying is well known to researchers in Andalusia:(I was not looking for fame and did not want it, I wanted the Muslim to know his history through what I present to him) is Professor Dr. Abdul Rahman Ali Al-Hajji from the people of Muqdadiya, as he wrote several pages in his books on the situation of Muslims after the fall of Granada (897 AH / 1492 AD), Which was represented in their emigration and expelling them from the land of Andalusia to the Maghreb, leaving everything they owned in their hands to the Christians after the conditions worsened for them. Three years after the Christianization operations began, Muslims were prevented from practicing their Islamic faith, which forced the Muslim to show Christianity and the secrets of Islam, and these are called Moriscos in order to preserve their religion, in addition to the burning of books in the year (904 AH / 1498 AD) in Bab al-Ramla Square, and the issuance of decrees forbidding Muslims to speak Arabic And other things, and as a result of that, there were several revolutions
Keywords: Hajji, his efforts, the Inquisition